Efektivitas Inokulasi Rhizobium sp. terhadap Pertumbuhan dan Hasil Kedelai pada Tanah Jenuh Air - - Jumrawati (Pusbindiklat - LIPI, 2010)
The effectiveness of Rhizobium sp. inoculation in several periodes of soil saturation on growth and yield of soybean were studied at green house experiment. This research was designed by using 2x6 faktorial treatment arranged in Completely Randomized Design (CRD) and two treatment i.e. without and with Rhizobium sp. inoculation. Ist factor was duration of soil saturation consisted of six treatments i.e. field capacity, water saturation for 5-10 days after planting (dap), 10-15 dap, 15-20 dap, 20-25 dap, and 25-30 dap. Several parameters including root nodule formation, activity of root nodul, growth and yield of soybean were observed. All data was analyzed by F-test and subjected to Duncan Multiple Range Test (DMRT) analysis at 5 % level when the treatments showing significantly variations. The result showed that Rhizobium sp. inoculation increased the amount of root nodule and activity of root nodule in fixing atmospheric nitrogen.